A highly flame-retardant ceramic silicone foam material and its application
By using modified silicon ash and low -molten glass powder, highly flame -retardant ceramic silicone foam material, the problem of poor flame retardability, poor porcelain effect, and uneven bubbles of the existing materials, and the high flame retardant performance And good porcelain effect.
Patent Information
- Application Number
- CN202411245170.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing flame-retardant ceramicized silicone foam materials have problems such as poor flame retardancy, poor porcelain formation effect, low foaming ratio and uneven bubble cells. Especially after high-temperature burning, the material is prone to deform, collapse or break.
Adopt high flame -retardant ceramic silicone foaming materials composed of base gum, ethylene silicone oil, hydrogen -containing silicone oil, reinforced filler, flame retardant fillers, composite ceramic powder, foaming agent, inhibitors and catalysts. The complexity of low -molten glass powder forms a nano -level cover layer and low temperature dense layer, which improves the compatibility, decentralization and thermal stability of the material.
A high flame -retardant performance, good porcelain effect, and uniform bubble structure can be achieved. The material can form a complete ceramic body at a low temperature of 700 ° C. After the high temperature is burned, it still maintains a good bubble structure and mechanical strength.
Smart Images

Figure CN118755272B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone rubber, and in particular to a highly flame-retardant ceramic silicone foam material and application thereof. Background Art
[0002] The technical key of new energy electric vehicles lies in the charging and discharging technology and safety performance of high energy density lithium batteries of electric vehicles. Improving the safety, stability, service life and endurance of automotive power battery systems is the key to the development of new energy vehicles. In order to fully ensure the safety of batteries, it is necessary to avoid damage to power battery packs caused by mechanical shock, short circuit, high temperature vehicle environment and other factors, which further lead to risks such as thermal runaway, spontaneous combustion and explosion. Therefore, it is necessary to provide batteries with good buffering, shock absorption, fireproof and heat insulation protection measures.
[0003] Silicone foam material has good softness, ultra-low stress, extremely low density, excellent resistance to compression permanent deformation, and excellent aging and weather resistance. It can be used as various types of buffering, shock absorption, support, sound insulation, heat preservation, insulation sealing and fireproof materials. It is widely used in new energy vehicles, wind power, electronic components, transportation tracks, aerospace and other fields. Flame-retardant ceramic silicone foam material is an improvement on the flame-retardant silicone foam. It can quickly form a ceramic body with a supporting structure at a high temperature of more than 600°C, and even maintain a hard ceramic shell without cracks or breaks after continuous calcination at a high temperature of 900-1000°C for 1-2 hours. At the same time, due to the unique pore structure and low thermal conductivity, it can prevent the generated heat from spreading quickly and play a role in heat insulation.
[0004] Ceramic foamed silicone has the problems of poor flame retardancy, poor ceramic effect, low foaming ratio, and uneven pores, especially low density (less than 0.5g / cm 3 ) In the case of low thickness (0.5mm to 3mm thickness), the flame retardancy is worse and the bubbles are more uneven. There are also defects such as bubble collapse and deformation, material deformation and shrinkage, and even fracture and powderization after high-temperature burning. At present, most of the production processes of flame-retardant ceramic foams are high-temperature solid silicone rubber compression foaming, which has high curing requirements, complex extrusion process, and difficult to control compression process. It is easy to produce uneven bubbles, which affects the thermal insulation effect after porcelain formation. Flame retardancy and porcelain effect are two independent properties. The use of fillers complements each other. Flame retardant fillers affect the porcelain effect to a certain extent, and vice versa. At the same time, the introduction of porcelain fillers affects the foaming of foam materials, which will make the system difficult to foam, or the bubbles are uneven, which increases the density of the material, thereby affecting the performance of ceramic foam materials, and not using ceramic silicone foam in lightweight technology in the field of new energy vehicles. Summary of the invention
[0005] In view of the problems and shortcomings in the prior art, the purpose of the present invention is to provide a highly flame-retardant ceramic silicone foam material and its application.
[0006] To achieve the purpose of the invention, the technical solution adopted by the present invention is as follows:
[0007] The first aspect of the present invention provides a highly flame-retardant ceramic silicone foam material, which is mainly made of the following raw materials in parts by weight: 50 parts of base rubber, 20-40 parts of vinyl silicone oil, 1-8 parts of hydrogen-containing silicone oil, 5-20 parts of reinforcing filler, 20-40 parts of flame-retardant filler, 0.5-3 parts of foaming agent, 60-100 parts of composite ceramic powder, 0.02-0.1 parts of inhibitor, and 0.1-1 parts of catalyst.
[0008] Furthermore, the highly flame-retardant ceramic silicone foam material also includes 0 to 20 parts of pigment and / or functional additive.
[0009] Preferably, the composite ceramic powder is compounded by low-temperature glass powder, polysilsesquioxane-modified wollastonite, and zinc borate in a mass ratio of (20-30): (50-70): (5-8).
[0010] Preferably, the low-temperature glass powder has a melting temperature of 400-600° C. and a particle size of 325 mesh to 2000 mesh.
[0011] Preferably, the preparation steps of the polysilsesquioxane-modified wollastonite are as follows: weigh 2500-3500 parts of dehydrated water, 2-5 parts of methanol and 1-5 parts of 5% hydrochloric acid solution, add them into a 5L three-necked flask, and control the temperature at 10-25°C for mechanical stirring; then, 5-10 parts of a mixture of methyltrimethoxysilane and vinyltrimethoxysilane, with a mixing mass ratio of 3:1, are added dropwise into the reactor to react for 1-3 hours; after raising the temperature to 60-80°C, 1000-1500 parts of wollastonite powder are added, stirring is started, and 0.2-2 parts of sodium hydroxide are added after 10 minutes, and stirring is continued for 4-8 hours at a low stirring speed of 80-120rpm; then, heating is stopped and cooled to room temperature, and the mixture is left to stand and wait for stratification; the water phase is removed, and the solid phase is washed with water and vacuum dried at 150°C for 2h to obtain the polysilsesquioxane-modified wollastonite.
[0012] Preferably, the aspect ratio of the wollastonite is 5:1 to 15:1, and the particle size is 325 to 2500 meshes.
[0013] Preferably, the foaming agent is mainly prepared from a nonionic silicone surfactant, polyvinyl pyrrolidone K30 with a water content of 98%, dimethyl silicone oil, and precipitated silica.
[0014] More preferably, the foaming agent preparation steps are:
[0015] (1) Preparation of nonionic silicone surfactants:
[0016] The side hydrogen-containing silicone oil of the following structural formula was selected as the starting material, wherein the molar content of hydrogen element in Si-H was 0.14%.
[0017]
[0018] Weigh 100g of hydrogenated silicone oil and 200g of isopropanol into a 500ml four-necked flask, pass cooling water, N2 protection, heat to 90℃, add 8ppm of Custer catalyst, mix for 2min, and then drop a mixture of 5.35g of 1-octene and 135.6g of allyl polyoxyethylene polyoxypropylene ether. [Polyether structure CH2=CHCH2O(C2H4O)8-(C3H6O) 18 -CH3)], after the addition is completed, reflux at 90°C for 10h to a translucent system, and then stop the reaction. Under the temperature condition of 100-110°C, the isopropanol is distilled out under reduced pressure of -0.09 to -0.1MPa, and the remaining substances in the reaction container are collected to obtain a transparent liquid nonionic silicone surfactant with an HLB of 3.75;
[0019] (2) Prepare 100 g of a polyvinyl pyrrolidone K30 mixture with a water content of 98%, stir evenly and set aside;
[0020] (3) Weigh 100 g of dimethyl silicone oil (dynamic viscosity at 25°C: 350 cp) and 5 g of precipitated silica (specific surface area: 200), disperse at high speed for 5 minutes, add 3 g of the nonionic surfactant in step (1), and mix for another 5 minutes. Add the mixture in step (2) to the system within 10 to 15 minutes, and continue stirring for 10 minutes to obtain a foaming agent.
[0021] Preferably, the base rubber is mainly kneaded from vinyl silicone oil, white carbon black and a structuring control agent.
[0022] More preferably, the preparation steps of the base glue are:
[0023] Add vinyl silicone oil, white carbon black and structuring control agent into a kneader and knead into a base rubber with high filler content for 2 to 4 hours. After neutralization by adding water, remove small molecules in the base rubber under vacuum conditions of -0.09 to -0.1 MPa and 130 to 150°C, then cool to 20 to 40°C and seal for storage.
[0024] Preferably, the vinyl silicone oil is methyl vinyl silicone oil having a dynamic viscosity of 500 to 20,000 cp at 25° C., and the methyl vinyl silicone oil is at least one of terminal vinyl silicone oil, side vinyl silicone oil, and terminal side vinyl silicone oil.
[0025] More preferably, the vinyl silicone oil has a vinyl molar content of 0.1% to 3.0%.
[0026] Preferably, the hydrogen-containing silicone oil is at least one of methyl hydrogen-containing silicone oil with a dynamic viscosity of 10 to 500 cp at 25°C, C1 to C18 straight or branched alkyl modified hydrogen-containing silicone oil, and C3 to C20 cycloalkyl modified hydrogen-containing silicone oil, and the hydrogen-containing silicone oil is at least one of terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil, and terminal-side hydrogen-containing silicone oil.
[0027] More preferably, the molar hydrogen content of the hydrogen-containing silicone oil is 0.05% to 1.5%.
[0028] Preferably, the reinforcing filler is silicon micropowder or MQ silicone resin.
[0029] More preferably, the MQ silicone resin is methyl MQ resin or vinyl MQ resin.
[0030] Preferably, the flame retardant filler is halogen-free flame retardant powder.
[0031] More preferably, the halogen-free flame retardant powder is at least one of aluminum hydroxide, magnesium hydroxide, surface-modified aluminum hydroxide, and surface-modified magnesium hydroxide.
[0032] Preferably, the inhibitor is one of acetylenic alcohol compounds, polyvinyl compounds, maleate compounds, and triphenylphosphine oxide.
[0033] More preferably, the inhibitor is one of 3-methyl-1-butyn-3-ol, trimethyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, 3-phenyl-1-butyn-3-ol, tetravinylcyclotetrasiloxane, octavinylcyclotetrasiloxane, maleate, and triphenylphosphine oxide.
[0034] Preferably, the catalyst is a di(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum complex diluted with isopropanol, methyl silicone oil, vinyl silicone oil, or chloroplatinic acid diluted with isopropanol. The structural formula of the di(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum complex is as follows.
[0035]
[0036] Preferably, the pigment can be a natural pigment such as cinnabar, red clay, realgar, malachite green, or a synthetic pigment such as red iron oxide, titanium dioxide, iron blue, which does not affect the performance of the catalyst; and the functional additive is graphene.
[0037] The method for preparing the above-mentioned highly flame-retardant ceramic silicone foam material comprises the following steps:
[0038] (1) Weigh 50 parts of base rubber, 20-40 parts of vinyl silicone oil, 1-8 parts of hydrogenated silicone oil, 5-10 parts of reinforcing filler, 20-40 parts of flame retardant filler, and 60-100 parts of composite ceramic powder in order by weight, stir and mix them for the first time, then add 0.02-0.1 parts of inhibitor, 0.5-3 parts of foaming agent, and 0-20 parts of pigment and / or functional additive, stir and mix them for the second time, then add 0.1-1 parts of catalyst, and stir and mix them for the third time to obtain a mixed material;
[0039] (2) The material in (1) is calendered and formed, and subjected to primary curing and secondary vulcanization to obtain a highly flame-retardant ceramic silicone foam material.
[0040] Preferably, the first stirring temperature is 20-40°C, and the stirring time is 20-40 min; the second stirring temperature is room temperature 20-30°C, and the stirring time is 5-10 min; and the third stirring time is 1-3 min.
[0041] Preferably, the primary curing temperature is 100-120° C., and the curing time is 8-12 min; the secondary vulcanization temperature is 190-200° C., and the vulcanization time is 10-20 min.
[0042] The second aspect of the present invention provides the application of the above-mentioned highly flame-retardant ceramic silicone foam material in the fields of new energy vehicle power batteries, transportation tracks, and electronic devices.
[0043] Compared with the prior art, the present invention has the following positive and beneficial effects:
[0044] 1) The present invention uses vinyl polysilsesquioxane to modify wollastonite. Through the modification, the outer layer of wollastonite with a large aspect ratio is formed into a nano-scale coating state, thereby increasing the compatibility and dispersibility of wollastonite with silicone rubber; the outer layer of wollastonite containing reactive functional groups can strengthen the connectivity between the powder and the silicone rubber, while the nano-size effect of the coating layer improves the mechanical strength of the foamed silica gel; in addition, the larger steric hindrance effect of polysilsesquioxane and the interaction between siloxane molecular chains can hinder the decomposition of polysiloxane at high temperature to form cyclic small molecules, thereby improving thermal stability and avoiding the phenomenon of shell cracking during high-temperature calcination into porcelain; at the same time, the vinyl polysilsesquioxane-modified wollastonite is compounded with ceramic powder to form a ceramic dense layer on the surface of the silicone rubber, thereby preventing thermal oxidation reaction and improving the residual rate of the ceramic body.
[0045] 2) The composite ceramic powder provided by the present invention is composed of low-melting glass powder, vinyl polysilsesquioxane modified wollastonite, and zinc borate. The low-melting glass powder is melted under low temperature conditions to form a liquid phase, which is used to encapsulate the decomposition products of the ceramic filler and the flame retardant filler. The fluid phase silicone rubber decomposes the silicon dioxide in the gaps, thereby reducing the ceramic formation temperature and forming a dense layer; the flame retardant low-melting point zinc borate is used as a bridging agent to assist the glass powder in forming a low-temperature dense layer. Polysilsesquioxane modified wollastonite is combined with zinc borate to improve the flame retardant properties, reduce the amount of inorganic flame retardant fillers added, and improve the mechanical properties of silicone rubber.
[0046] 3) The material provided by the present invention can form a complete ceramic body at a low temperature of 700°C, with a smooth surface and high flame retardancy. At the same time, the material has an excellent foaming effect, uniform pores, and still maintains a good pore structure after high-temperature calcination. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a diagram of the ceramic structure of the sample in Example 1 of the present invention after calcination at 700° C. for 2 hours;
[0048] Figure 2 This is a ceramic structure diagram of the sample in Example 1 of the present invention after calcination at 900° C. for 2 hours;
[0049] Figure 3 This is a ceramic structure diagram of the sample in Example 4 of the present invention after calcination at 700° C. for 2 hours;
[0050] Figure 4 This is the ceramic structure diagram of the sample in Comparative Example 2 after calcination at 700°C for 2h;
[0051] Figure 5 This is the ceramic structure diagram of the sample in Comparative Example 3 after calcination at 700°C for 2h;
[0052] Figure 6 This is the appearance diagram of the cross section of the foamed hole of the sample in Comparative Example 4;
[0053] Figure 7 This is the ceramic structure diagram of the sample in Comparative Example 5 after calcination at 700°C for 2 hours. DETAILED DESCRIPTION
[0054] Preparation:
[0055] 1. Preparation of base glue:
[0056] Weigh 70 parts of vinyl silicone oil (vinyl molar content 0.31%) with a dynamic viscosity of 20000cp at 25°C and a specific surface area of 200m 2 / g of fumed silica 29 parts and 2.5 parts of octyltrimethoxysilane, a structuring control agent, are kneaded in a kneader and heated to 150°C for 2 hours. The small molecules in the base rubber are then removed under vacuum conditions of -0.095MPa and 160°C. The temperature is then lowered to below 40°C, sealed and stored for later use.
[0057] Preparation of foaming agent:
[0058] S1 Preparation of nonionic silicone surfactant:
[0059] The side hydrogen-containing silicone oil of the following structural formula was selected as the starting material, wherein the molar content of hydrogen element in Si-H was 0.14%.
[0060]
[0061] Weigh 100g of hydrogenated silicone oil and 200g of isopropanol into a 500ml four-necked flask, pass cooling water, N2 protection, heat to 90℃, add 8ppm of Custer catalyst, mix for 2min, and then drop a mixture of 5.35g of 1-octene and 135.6g of allyl polyoxyethylene polyoxypropylene ether. [Polyether structure CH2=CHCH2O(C2H4O)8-(C3H6O) 18 -CH3)], after the addition was completed, the mixture was refluxed at 90°C for 10 hours until a semi-transparent system was formed, and the reaction was stopped. Isopropanol was distilled out under reduced pressure at 105°C and a vacuum degree of -0.095MPa, and the remaining substances in the reaction container were collected to obtain a transparent liquid nonionic silicone surfactant with an HLB of 3.75.
[0062] Preparation of foaming agent:
[0063] (S2-1) Prepare 100 g of a polyvinyl pyrrolidone K30 mixture having a water content of 98%, stir well and set aside;
[0064] (S2-2) Weigh 100 g of dimethyl silicone oil (dynamic viscosity at 25°C: 350 cp) and 5 g of precipitated silica (specific surface area: 200), disperse at high speed for 5 minutes, add 3 g of the nonionic silicone surfactant in step (S1), and mix for another 5 minutes. Add the mixture in step (S2-1) to the system, and continue stirring for 10 minutes to obtain a foaming agent.
[0065] Preparation of polysilsesquioxane modified wollastonite:
[0066] Weigh 2500 parts of deionized water, 4 parts of methanol and 3 parts of 5% hydrochloric acid solution, add them to a 5L three-necked flask, control the temperature at 25°C and mechanically stir and mix for 10 minutes; then add 10 parts of a mixture of methyltrimethoxysilane and vinyltrimethoxysilane (mixing mass ratio 3:1) dropwise into the reactor, and keep the temperature at 15°C for 2 hours. After raising the temperature to 80°C, add 1200 parts of wollastonite powder, start stirring, add 0.8 parts of sodium hydroxide after 10 minutes, maintain a low stirring speed of 80rpm and continue stirring for 5 hours. Then stop heating and cool to room temperature 25°C, stand still for 6 hours and wait for stratification. Remove the water phase, wash the powder with deionized water 3 times, and then vacuum dry it at 150°C for 2 hours to obtain polysilsesquioxane-modified wollastonite powder.
[0067] Example 1
[0068] A highly flame-retardant ceramic silicone foam material is made from the following raw materials in parts by weight:
[0069] 50 parts of base glue,
[0070] 40 parts of vinyl silicone oil (dynamic viscosity at 25°C is 1000cp, vinyl molar content is 0.91%),
[0071] 6 parts of hydrogenated silicone oil (dynamic viscosity at 25°C is 56cp, silicon-hydrogen molar content is 0.5%),
[0072] 8 parts of methyl MQ resin (M / Q ratio is 0.8, dynamic viscosity at 25°C is 12000cp, vinyl content is 0.8%),
[0073] 20 parts of aluminum hydroxide (particle size 3000 mesh),
[0074] 90 parts of composite ceramic powder,
[0075] 1 part of foaming agent,
[0076] 0.2 parts of tetravinylcyclotetrasiloxane,
[0077] 0.1 part of Custer catalyst (0.5% platinum content).
[0078] The composition of the composite ceramic powder used is shown in Table 1.
[0079] Table 1 Compound ceramic powder 1
[0080]
[0081] The steps for preparing the above-mentioned highly flame-retardant ceramic silicone foam material are as follows:
[0082] 1) Weigh 50 parts of base rubber, 40 parts of vinyl silicone oil, 6 parts of hydrogenated silicone oil, 8 parts of methyl MQ resin, 20 parts of aluminum hydroxide, and 90 parts of composite ceramic powder in sequence and add them into a planetary mixer, start stirring, control the temperature below 40°C, mix for 30 minutes, then add 1 part of foaming agent and 0.2 parts of tetravinylcyclotetrasiloxane, stir for 10 minutes at room temperature below 40°C, stir evenly, add 0.1 parts of Custer catalyst, stir and mix for 3 minutes, then stop stirring;
[0083] 2) The material in 1) is calendered into a calender covered with release paper to a thickness of 1±0.2 mm, and then placed in a drying oven at 100°C for curing for 10 minutes, and then the release papers on the upper and lower sides are peeled off;
[0084] 3) The foam material in step 2) is placed in a drying oven at 190° C. for secondary vulcanization for 10 minutes to obtain a highly flame-retardant ceramic silicone foam material.
[0085] The prepared samples were calcined at 700℃ and 900℃ for 2h, and the structure of the ceramic body was shown in Figure 2. Figure 1 and Figure 2 From the figure, it can be seen that the sample forms a ceramic body at 700℃ with a smooth surface. After calcination at a high temperature of 900℃, it still maintains a good ceramic support structure, complete pores and a small bending angle.
[0086] Example 2
[0087] The content of a highly flame-retardant ceramic silicone foam material is substantially the same as that of Example 1, except that the foaming agent is 3 parts.
[0088] Example 3
[0089] The content of a highly flame-retardant ceramic silicone foam material is substantially the same as that of Example 1, except that the amount of the composite ceramic powder is 65 parts.
[0090] Example 4
[0091] A highly flame-retardant ceramic silicone foam material is made from the following raw materials in parts by weight:
[0092] 50 parts of base glue,
[0093] 25 parts of vinyl silicone oil (dynamic viscosity at 25°C is 1000cp, vinyl molar content is 0.91%),
[0094] 4 parts of hydrogenated silicone oil (dynamic viscosity at 25°C is 45cp, silicon-hydrogen molar content is 0.8%),
[0095] 5 parts of methyl MQ resin (M / Q ratio = 0.75, dynamic viscosity at 25°C is 10000),
[0096] 35 parts of aluminum hydroxide (particle size 1200 mesh),
[0097] 60 parts of composite ceramic powder,
[0098] 0.2 parts of black paste,
[0099] 2 parts of foaming agent,
[0100] 0.4 parts of tetravinylcyclotetrasiloxane,
[0101] 0.5 parts of Custer catalyst (0.5% platinum content).
[0102] The composition of the composite ceramic powder used is shown in Table 2.
[0103] Table 2 Compound ceramic powder 2
[0104]
[0105] 1) Weigh 50 parts of base rubber, 25 parts of vinyl silicone oil, 4 parts of hydrogenated silicone oil, 5 parts of methyl MQ resin, 35 parts of aluminum hydroxide, 60 parts of composite ceramic powder, and 0.2 parts of black slurry in sequence and add them into a planetary mixer, start stirring, control the temperature below 40°C, mix for 30 minutes, then add 2 parts of foaming agent and 0.4 parts of tetravinylcyclotetrasiloxane, stir for 10 minutes at room temperature below 40°C, stir evenly, add 0.5 parts of Custer catalyst, stir and mix for 3 minutes, then stop stirring;
[0106] 2) The material in 1) is calendered into a calender covered with release paper to a thickness of 0.3±0.1 mm, and then placed into a drying oven at 90°C for curing for 10 minutes, and then the release papers on the upper and lower sides are peeled off;
[0107] 3) The foam material in step 2) is placed in a drying oven at 190° C. for secondary vulcanization for 10 minutes to obtain a flame-retardant ceramic silicone foam.
[0108] The prepared sample was calcined at 700℃ for 2h, and the structure of the ceramic body was Figure 3 ,From the figure, it can be seen that the structure of the ceramic body is complete, the surface is flat, and the bending angle is small.
[0109] Example 5
[0110] The content of a highly flame-retardant ceramic silicone foam material is basically the same as that of Example 4, except that a hydrogenated silicone oil with a dynamic viscosity of 28 cp at 25° C., a silicon-hydrogen molar content of 1.58%, and a dosage of 1.5 parts is selected.
[0111] Example 6
[0112] The content of a highly flame-retardant ceramic silicone foam material is substantially the same as that of Example 4, except that the inhibitor is 0.2 parts of a mixture of 3-methyl-1-butyn-3-ol in which octamethylcyclotetrasiloxane is diluted 20 times.
[0113] Test standard:
[0114] Tensile strength, elongation: GB / T1701-2001 "Determination of tensile strength and elongation at break of hard rubber" standard tests the tensile strength and elongation at break of foam materials.
[0115] Foam density: The density of the foam material is measured using an electronic analytical balance in accordance with GB / T 533-2008 "Test for density of vulcanized rubber or thermoplastic rubber".
[0116] Foaming ratio: Pour the silicone rubber foaming composition material stirred after adding the catalyst component into a graduated measuring cup quickly, record the material height L0, and record the material height L1 after foaming is complete. Calculate L1 / L0 to be the foaming ratio of the silicone foam material.
[0117] Flame retardant test: UL94-2009 "Flammability Test for Plastic Materials for Equipment and Appliance Components" standard tests flame retardant properties.
[0118] The expansion rate after ablation is measured by a thickness gauge. Expansion rate = (thickness after ablation - thickness before ablation) / thickness before ablation * 100%
[0119] The residual content is tested using an analytical balance, residual content = mass after erosion / (mass before erosion)*100%, the mass after erosion is the remaining mass of the sample after oscillation.
[0120] Ceramic grade assessment: Take a test piece with a thickness of 2-3mm. There is no clear specification for the shape. It can be a 50*50cm square sample or a 40*60cm rectangular sample. Place it in a 700℃ muffle furnace for 2 hours to observe its ceramic state, including whether the ceramic structure is complete, whether the surface is flat, the degree of curvature, and the change of the pores. The assessment levels are as follows:
[0121] Ceramic grade 1: The ceramic body is intact, the surface is smooth and without cracks, the bending angle is less than 5°, and there is no breakage when falling;
[0122] Ceramic grade 2: The ceramic body is intact, with slight cracks or protrusions on the surface, the whole is flat, the bending angle is less than 10°, and there is no cracking when falling;
[0123] Ceramic grade 3: The ceramic body is intact, with slight bumps or cracks on the surface, no breakage when dropped, and the bending angle is greater than 10° and less than 20°;
[0124] Ceramic grade 4: A ceramic body can be formed, with a large number of concave and convex points on the surface or a large amount of flocculent dust, or it falls and breaks, or the bending angle is greater than 20°;
[0125] Ceramic grade 5: The ceramic body has severe cracks or breaks when dropped or is bent more than 30° or has a severely uneven surface.
[0126] The samples prepared in Examples 1 to 6 were tested according to the above test standards, and the performance test results of the samples are shown in Table 3.
[0127] Table 3 Performance test table of Examples 1 to 6
[0128]
[0129] It can be seen from the test results in Table 3 that compared with Example 1, when the amount of composite ceramic powder is the same, Example 2 increases the amount of foaming agent to increase the foaming ratio of the material, reduce the material density, and slightly reduce the residual amount, but does not affect the ceramic structure of the material. Example 3 reduces the amount of composite ceramic powder to the range specified in the patent on the basis of Example 1, which will reduce the density of the foamed material and also reduce the residual amount after calcination, causing the thickness of the ceramic body after calcination to expand to a certain extent, but the structure of the ceramic body is intact. Example 4 changes the addition ratio of glass powder, modified wollastonite and zinc borate, and can also obtain a foamed material with a low-density ceramic structure. Example 5 only changes the structure of hydrogenated silicone oil on the basis of Example 4, using high hydrogenated silicone oil, which reduces the density of the foamed material and does not affect the ceramic structure of the material. Example 6 changes the type of inhibitor on the basis of Example 4, affecting the material density but not the ceramic structure of the material. It can be seen from Examples 1 to 6 that the amount of composite ceramic powder used affects the density of the material. The more the amount used, the higher the material density and the lower the foaming ratio. However, it will increase the residual amount of the material after high-temperature calcination and reduce the expansion rate of the material.
[0130] Comparative Example 1
[0131] The content of a silica gel foam material is substantially the same as that of Example 1, except that: the composite ceramic powder is 0 parts, that is, no composite ceramic powder is added.
[0132] Comparative Example 2
[0133] The content of a silica gel foam material is substantially the same as that of Example 1, except that: the composite ceramic powder is 30 parts.
[0134] The prepared sample was calcined at 700℃ for 2h, and the structure of the ceramic body was Figure 4,It can be seen from the figure that the amount of composite ceramic powder added is insufficient (within the scope specified by the patent), the ceramic effect of the material is poor, the surface is powdered or a large number of bubbles appear.
[0135] The performance of the samples prepared in Comparative Example 1 and Comparative Example 2 was tested, and the test results are shown in Table 4.
[0136] Table 4 Performance test table of comparative examples 1 and 2 and embodiment 1
[0137]
[0138] From the test results in Table 4, it can be found that when the system does not add the composite ceramic powder, the ceramic body cannot be formed at all. When the addition amount of the composite ceramic powder is too low, the vitrification effect of the ceramic body is poor, the shell is easy to break, and the stability is poor.
[0139] Comparative Example 3
[0140] The content of a silica gel foam material is substantially the same as that of Example 3, except that the aluminum hydroxide is 50 parts. The performance test results are shown in Table 5.
[0141] Table 5 Performance test table of comparative example 3 and embodiment 3
[0142]
[0143] From the test results in Table 5, it can be found that excessive addition of flame-retardant powder aluminum hydroxide affects the ceramicization effect. During the burning process of the sample, the flame-retardant powder aluminum hydroxide produces a large amount of decomposition products, which cannot be well combined with the composite ceramic powder to form a dense protective layer, thereby reducing the residual amount after burning.
[0144] The prepared sample was calcined at 700℃ for 2h, and the structure of the ceramic body was Figure 5 It can be seen from the figure that the material can form a ceramic structure, but the flame retardant powder aluminum hydroxide is added excessively. The low-temperature glass powder in the ceramic powder cannot completely cover the decomposition product of aluminum hydroxide after melting into a liquid phase, and a large amount of flocs exist on the surface after high-temperature calcination.
[0145] Comparative Example 4
[0146] The content of a silica gel foam material is substantially the same as that of Example 4, except that the composite ceramic powder is 105 parts.
[0147] The performance test results are shown in Table 6.
[0148] Table 6 Performance test table of comparative example 4 and embodiment 4
[0149]
[0150] From the test results in Table 6, it can be found that increasing the amount of composite ceramic powder increases the burning residue of the foam material, but causes the density of the foam material to be too high and the pores to be uneven, which affects the use effect of the material.
[0151] The cross section of the foamed hole of the sample prepared in this comparative example is shown in FIG. Figure 6 ,From the figure, it can be seen that the amount of ceramic powder is too large, the pore size of the material is uneven, and the pore collapse is serious.
[0152] Comparative Example 5
[0153] The content of a silica gel foam material is substantially the same as that of Example 4, except that this comparative example uses conventional unmodified wollastonite with an aspect ratio of 4:1. The performance test results are shown in Table 7.
[0154] Table 7 Performance test table of comparative example 5 and embodiment 4
[0155]
[0156] From the test results in Table 7, it can be found that when the polysilsesquioxane-modified wollastonite with a large aspect ratio is replaced with the unmodified wollastonite with a normal aspect ratio, the bending angle of the ceramic body after calcination increases, the residual volume decreases, cracks appear, and the expansion rate increases significantly. The results are shown in the attached Figure 7 This indicates that the polysilsesquioxane-modified wollastonite of the present invention can increase the residual amount of the ceramic body, reduce the expansion degree during the burning process, and enhance the ceramicization effect.
[0157] The preparation method of high-resistance ceramic silicone foam material provided by this patent can obtain low-density ceramic foam material with good ceramic effect, small curvature and good flame retardant performance. It can be used in new energy vehicle power batteries and battery components for heat insulation, fire prevention, buffering, shock absorption, support and sound insulation.
Claims
1. A highly flame retardant ceramic silicone foam material, characterized in that: The invention is mainly made of the following raw materials in parts by weight: 50 parts of base rubber, 20-40 parts of vinyl silicone oil, 1-8 parts of hydrogenated silicone oil, 5-20 parts of reinforcing filler, 20-40 parts of flame retardant filler, 0.5-3 parts of foaming agent, 60-100 parts of composite ceramic powder, 0.02-0.1 parts of inhibitor and 0.1-1 parts of catalyst; the composite ceramic powder is compounded by low-temperature glass powder, polysilsesquioxane-modified wollastonite and zinc borate in a mass ratio of (20-30): (50-70): (5-8); the foaming agent is mainly prepared by non-ionic silicone surfactant, polyvinyl pyrrolidone with a water content of 98%, dimethyl silicone oil and precipitated silica.
2. The highly flame-retardant ceramic silicone foam material according to claim 1, characterized in that: The melting temperature of the low-temperature glass powder is 400-600° C., and the particle size is 325 meshes-2000 meshes.
3. The highly flame-retardant ceramic silicone foam material according to claim 1, characterized in that: The preparation steps of the polysilsesquioxane-modified wollastonite are as follows: 2500-3500 parts of water, 2-5 parts of methanol and 1-5 parts of 5% hydrochloric acid solution are stirred at 10-25°C; then 5-10 parts of a mixture of methyltrimethoxysilane and vinyltrimethoxysilane are added dropwise, wherein the mass ratio of methyltrimethoxysilane to vinyltrimethoxysilane is 3:1, and the mixture is reacted for 1-3 hours; then 1000-1500 parts of wollastonite powder are added at a temperature of 60-80°C, 0.2-2 parts of sodium hydroxide are added after stirring evenly, and stirring is continued for 4-8 hours; finally, the mixture is cooled to room temperature, allowed to stand for stratification, the aqueous phase is removed, the solid phase is washed with water, and then vacuum dried at 150°C for 2 hours to obtain the polysilsesquioxane-modified wollastonite.
4. The highly flame-retardant ceramic silicone foam material according to claim 1, characterized in that: The base rubber is mainly prepared by kneading vinyl silicone oil, white carbon black and a structuring control agent.
5. The highly flame-retardant ceramic silicone foam material according to claim 1, characterized in that: The vinyl silicone oil is a methyl vinyl silicone oil with a dynamic viscosity of 500 to 20,000 cp at 25°C, and a vinyl molar content of 0.1% to 3.0% in the methyl vinyl silicone oil; the hydrogen-containing silicone oil has a dynamic viscosity of 10 to 500 cp at 25°C, and a hydrogen molar content of 0.05% to 1.5%.
6. The highly flame-retardant ceramic silicone foam material according to claim 1, characterized in that: The reinforcing filler is silicon micropowder or MQ silicone resin; the flame retardant filler is halogen-free flame retardant powder; the inhibitor is one of acetylenic alcohol compounds, polyvinyl compounds, maleate compounds, and triphenylphosphine oxide; the catalyst is isopropyl alcohol, methyl silicone oil, di(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum complex diluted with vinyl silicone oil, or chloroplatinic acid diluted with isopropyl alcohol.
7. The highly flame-retardant ceramic silicone foam material according to claim 6, characterized in that: The MQ silicone resin is methyl MQ resin or vinyl MQ resin; the halogen-free flame retardant powder is at least one of aluminum hydroxide, magnesium hydroxide, surface-modified aluminum hydroxide, and surface-modified magnesium hydroxide; the inhibitor is one of 3-methyl-1-butyn-3-ol, trimethyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynyl-1-cyclohexanol, 3-phenyl-1-butyn-3-ol, tetravinylcyclotetrasiloxane, octavinylcyclotetrasiloxane, maleate, and triphenylphosphine oxide.
8. Application of the highly flame-retardant ceramic silicone foam material according to any one of claims 1 to 7 in the fields of new energy vehicle power batteries, transportation tracks, and electronic devices.
Citation Information
Patent Citations
Foam silicone rubber material and preparation method thereof
CN113214650A
Foamed silicone rubber sealing sheet and preparation method thereof
CN115216156A